2001
DOI: 10.1200/jco.2001.19.7.2074
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Phase Ib/II Trial of the Radiation Enhancer Motexafin Gadolinium in Patients With Brain Metastases

Abstract: Motexafin gadolinium was well tolerated at doses up to 6.3 mg/kg, was selectively accumulated in tumors, and, when combined with WBRT of 30 Gy in 10 fractions, was associated with a high radiologic response rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
2
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 121 publications
(88 citation statements)
references
References 0 publications
4
81
2
1
Order By: Relevance
“…MGd could therefore modulate a variety of downstream processes by mobilizing zinc. The importance of this would likely depend on the particular system under study but would be most likely to occur in tumors, where the drug seems to localize selectively (15)(16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MGd could therefore modulate a variety of downstream processes by mobilizing zinc. The importance of this would likely depend on the particular system under study but would be most likely to occur in tumors, where the drug seems to localize selectively (15)(16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…For example, motexafin gadolinium (MGd, Xcytrin, Fig. 1A), an expanded porphyrin containing the lanthanide cation gadolinium, is currently in clinical trials for the treatment of several forms of cancer (15)(16)(17)(18)(19)(20)(21)(22)(23). MGd is an electron-affinic compound that mediates electron transfer from a variety of intracellular reducing species, such as ascorbate, NADPH, and thiols, to oxygen to form superoxide and hydrogen peroxide (20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary studies in patients with brain metastases treated with motexafin gadolinium and WBRT showed radiologic responses in 68% to 72% of patients (40,68). A large randomized phase III study of motexafin gadolinium in 401 patients did not show a significant increase in median survival (5.2 versus 4.9 months; P = 0.48) or median time to neurologic progression (9.5 versus 8.3 months; P = 0.95).…”
Section: Prevention Of Neurocognitive Impairment: Enhancing Radiationmentioning
confidence: 96%
“…Motexafin gadolinium is a metalloporphyrin redox modulator that shows selective tumor localization and catalyzes the oxidation of a number of intracellular reducing metabolites, such as ascorbate, glutathione, and NADP + , thereby generating reactive oxygen species and depleting the pools of reducing agents necessary to repair cytotoxic damage (67). Selective uptake of motexafin gadolinium in tumors, but not in normal tissues, has been shown in patients by magnetic resonance imaging because of its paramagnetic characteristics (34,39,68,69).…”
Section: Prevention Of Neurocognitive Impairment: Enhancing Radiationmentioning
confidence: 99%
“…The company filed an investigational new drug (IND) application with the FDA to begin clinical testing of the drug in human patients. After a successful Phase I/II study, 62 the company began a Phase III study (called trial 9801) that enrolled patients with any type of cancerous tumor who developed brain metastases. Subjects were randomized to either whole brain radiation therapy (WBRT) alone (the control arm) or MGd and WBRT (treatment arm).…”
Section: A Background On Mgdmentioning
confidence: 99%